Sales Taxation and the Mints Plan - Bronfenbrenner, M. (The Review of Economics and Statistics, 1947)
Discussion regarding Professor L. W. Mints' recent monetary policy proposals I has been concentrated on his basic suggestion that contra-cyclical fiscal flexibility be attained primarily from the receipts side, with a substantially fixed budget of total expenditures. The present writer will limit himself to outlining an ancillary proposal that a general sales tax should figure prominently in any plan for contra-cyclical variations in tax receipts, and to a reconsideration of the case for sales taxation in the light of such a receipts policy. Professor Mints' plan includes a special device which suggests with particular force the desirability of a linkage with sales taxation. This is his proposed sales subsidy as a remedial measure for deep depressions. The sales subsidy is proposed despite the admitted administrative difficulty of superposing this negative tax on a Treasury without provision for collecting the corresponding positive levy. This particular feature of Mints' plan may be only an insignificant afterthought, since its author expects slumps to be controlled by less extreme monetary and fiscal measures.2 Yet even though Mints' own sales subsidy be disregarded as a superfluous gadget, definite reasons remain for preferring sales to income taxation as a vehicle for moderate contra-cyclical variation in receipts, just as Mints himself prefers the sales to the income subsidy as a vehicle for deflation control in extremis. In the discussion which follows, the normal (full employment, balanced budget, but nonboom) sales tax rate is envisaged as substantial, perhaps the io or 15 per cent suggested during World War II. Rate variations about the usual American state figures of two and three per cent can hardly be expected to have practical effects.